Transformative curriculum design in health sciences education - Halupa, Colleen (Hersey, PA Medical Information Science Reference, an imprint of IGI Global, 2015)
"This book provides information for faculty to learn how to translate technical competencies in medicine and healthcare into the development of both traditional and online learning environments"--Provided by publisher.
Includes bibliographical references (pages 346-376) and index.
Keywords: Medical education; Medical education -- Technological innovations; Curriculum planning; Medicine -- Study and teaching (Continuing education)